2013
DOI: 10.1002/mc.22120
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for the long non‐coding RNA GAS5 in proliferation and apoptosis in non‐small‐cell lung cancer

Abstract: In more recent years, long non-coding RNAs (lncRNAs) have been investigated as a new class of regulators of cellular processes, such as cell growth, apoptosis, and carcinogenesis. Although lncRNAs are dysregulated in numerous cancer types, limited data are available on the expression profile and functional role of lncRNAs in non-small cell lung cancer (NSCLC). In the present study, we determined the expression pattern of the growth arrest-specific transcript 5 (GAS5) in 72 NSCLC specimens by qRT-PCR and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
229
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(242 citation statements)
references
References 49 publications
(50 reference statements)
7
229
4
Order By: Relevance
“…For example, Cao et al noticed that patients with cervical cancer with reduced expression of GAS5 have significantly poorer overall survival than those with higher GAS5 expression (30). Shi et al reported that GAS5 expression was downregulated in non-small cell lung cancer tissues compared with that in noncancerous tissues, and was highly associated with tumor size and tumor-node-metastasis stage (31). However, in the present study, it was observed that the expression of GAS5 was upregulated in epithelial ovarian cancer compared with that in adjacent healthy tissues.…”
Section: Discussioncontrasting
confidence: 84%
“…For example, Cao et al noticed that patients with cervical cancer with reduced expression of GAS5 have significantly poorer overall survival than those with higher GAS5 expression (30). Shi et al reported that GAS5 expression was downregulated in non-small cell lung cancer tissues compared with that in noncancerous tissues, and was highly associated with tumor size and tumor-node-metastasis stage (31). However, in the present study, it was observed that the expression of GAS5 was upregulated in epithelial ovarian cancer compared with that in adjacent healthy tissues.…”
Section: Discussioncontrasting
confidence: 84%
“…11 Several studies showed that GAS5 was downregulated and served as a tumor suppressor in many kinds of cancers, such as breast cancer, prostate cancer, and lung cancer. [12][13][14] In addition, GAS5 was downregulated in cervical cancer tissues and knockdown of GAS5 promoted proliferation, migration, and invasion in cervical cancer cells. 15 Recently, a competing endogenous RNA (ceRNA) regulatory network has revealed that lncRNA function as a molecular sponge in regulating the expression and biological functions of miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that low expression of GAS5 is associated with a higher possibility of lymph node metastasis and distant metastasis in non-small cell lung cancer and gastric cancer, although the differences are not significant (P=0.652 and P=0.056, respectively) (17,19). These findings further suggest that lncRNA GAS5 may function as a tumor suppressor and may represent a potential biomarker and new therapeutic target for some cancers.…”
Section: Discussionmentioning
confidence: 84%
“…GAS5 was originally isolated from NIH 3T3 cells by Schneider et al with the purpose of identifying potential tumor suppressor genes enriched during growth arrest induced by serum starvation (10). GAS5 transcript levels are significantly reduced in a spectrum of cancers including breast, prostate, glioblastoma, renal clear cell, bladder, hepatocellular, pancreatic, non-small cell lung, colorectal, cervical and multiple myeloma (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Importantly, aberrant GAS5 expression was significantly correlated with metastasis in cervical cancer (21) and hepatocellular carcinoma (15).…”
Section: Introductionmentioning
confidence: 99%